Evaluation of Energy Recovery Potential by Anaerobic Digestion and Dark Fermentation of Residual Biomass in Colombia - Mónica Amado; Mónica Amado; Cristian Barca; Mario A. Hernández; Jean-Henry Ferrasse (Frontiers in Energy Research, 2021)
This study provides the first overview in Colombia on energy recovery potential by anaerobic digestion (AD) and dark fermentation (DF) of three different residual biomasses: coffee mucilage (CFM), cocoa mucilage (CCM), and swine manure (SM). First, AD and DF models were developed based on the ADM1 model. Then, simulated biogas production yields were compared to experimental data to validate the models. The results of comparative simulations indicate that energy recovery potentials from biogas for the different Colombian departments range from 148 to 48,990 toe, according to the local production amounts of CFM, CCM, and SM in 2017. The study provides crucial information that can be used to assess the best design, operation mode, and locations of AD and DF plants in Colombia. The results indicate that biogas production performances and energy recovery yields improve by increasing CFM/SM and/or CCM/SM ratios of the feed, and by increasing organic load from 2 to 26 gCOD∙l−1.